Potential of Soil Bacteria as Mercury Bioremediation Agent in Traditional Gold Mining - Winardi Winardi; Eko Haryono; Sudrajat Sudrajat; Endang Sutariningsih Soetarto (Biosaintifika: Journal of Biology & Biology Education, 2019)
Mandor Village has developed as a tradisional gold mining area since years ago. It involved activities that have led to extreme land condition and the release of mining residues, i.e., mercury, to the soils. The study examined the potential of soil bacteria as mercury bioremediation agent based on their population and activity in former mines with different ages. The bacterial population was measured by isolating soil bacteria on solid media using the pour plate method, and the colonies were enumerated during the incubation. The Nutrient Agar (NA) medium was used to obtain the total population, whereas the Salt Base Solution (SBS) was to determine the presence of mercury-tolerant bacteria. The addition of HgCl2 affected the number of the colonies. The colony only grew until the concentration of HgCl2 reached 5 mg/l, and the total colony was larger in older mines. The observation of bacterial activity showed that biotransformation performance was lower when the concentration of mercury was the same as its natural presence in soils (0.1-0.5 mg/l) compared with higher mercury level (1 mg/l). The research showed that lower mercury concentrations in nature reduced the natural ability of bacteria to transform pollutants. This study provides information that can assist the development of a technological approach to control mercury pollution in former traditional gold mines in an environmentally friendly manner using indigenous soil bacteria.